Hubungan Mekanisme Koping dengan Kecemasan pada Penderita Diabetes Melitus Tipe 2 di Kelurahan Nanggeleng Wilayah Kerja UPTD Puskesmas Nanggeleng Kota Sukabumi - Sari, Aulia Fatimah; Dewi, Rosliana; Huda, Akhmad (Jurnal Ragam Pengabdian, 2026)
Type II Diabetes Melitus is a chronic disease often called a "silent killer" that can cause serious complications. This condition frequently triggers anxiety in patients due to concerns about the long duration of the illness, the lengthy treatment process, and potential health risks. Coping mechanisms are a key factor influencing these anxiety levels. This study aims to determine the relationship between coping mechanisms and anxiety levels among type II Diabetes Melitus patients in Nanggeleng Village, Sukabumi City. This quantitative study used a correlational design with a cross-sectional approach. The sample consisted of 115 respondents selected through proportional random sampling. Data were collected using the Brief Cope Inventory for coping mechanisms and the Zung Self-Rating Anxiety Scale for anxiety levels. Data were analyzed using the Contingency Coefficient test. Most respondents had maladaptive coping mechanisms and experienced panic-level anxiety. Statistical analysis showed a significant relationship between coping mechanisms and anxiety, with a strong correlation. Patients with adaptive coping mostly had moderate anxiety, while those with maladaptive coping mostly experienced panic. There is a significant relationship between coping mechanisms and anxiety levels in type II Diabetes Melitus patients. Health workers are encouraged to provide psychological education to improve adaptive coping.